2021
DOI: 10.1111/trf.16711
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance of serious adverse events following transfusion of COVID‐19 convalescent plasma

Abstract: Background The reported incidence of adverse reactions following Coronavirus disease 2019 (COVID‐19) convalescent plasma (CCP) transfusion has generally been lower than expected based on the incidence of transfusion reactions that have been observed in studies of conventional plasma transfusion. This raises the concern for under‐reporting of adverse events in studies of CCP that rely on passive surveillance strategies. Materials and Methods Our institution implemented a protocol to actively identify possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several clinical trials have shown the safety of CCP administration. 7,20,21 Most CCP studies have used pre-vaccination CCP and had mixed outcomes 20,22,23 ; patients with comorbidities who received CCP early in the illness course were thought to have the most benefit. 24 A number of studies have examined high-titer CCP in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have shown the safety of CCP administration. 7,20,21 Most CCP studies have used pre-vaccination CCP and had mixed outcomes 20,22,23 ; patients with comorbidities who received CCP early in the illness course were thought to have the most benefit. 24 A number of studies have examined high-titer CCP in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%
“…One patient had a febrile nonhemolytic transfusion reaction, and another had transfusion‐associated circulatory overload with transient supplemental oxygen requirement via nasal prongs. Several clinical trials have shown the safety of CCP administration 7,20,21 …”
Section: Discussionmentioning
confidence: 99%
“…These include the common transfusion reactions, including HLA-, HNA- and HPA-antibodies. Several reports indicate that the risk of such reactions are not increased compared to regular transfusion reactions [22] , [23] . If several units of convalescent plasma were pooled, this could improve efficacy of the product and it would lead to standardisation [24] .…”
Section: Convalescent Plasma: International Covid-19 Pandemic Respons...mentioning
confidence: 99%
“…The most common adverse reactions are transfusion‐associated dyspnea and transfusion‐associated circulatory overload. Active surveillance can help mitigate under‐reporting of adverse reactions 9 …”
Section: Covid‐19 Convalescent Plasmamentioning
confidence: 99%